Adiponectin Level in Women with Breast Cancer - Homaee, Fatemeh; Ghaffarzadehgan, Kamran; Aziminia, Azar; Ghodrati, Hamideh; Izanloo, Azra; Ziaolhagh, Reza; Ardalan Khales, Sahar (Asian Pacific Journal of Cancer Biology, 2017)
Introduction: Adiponectin is one of the plasma protein derived from adipose tissue which has a positive effect on the metabolism of fat and lipid, resulting from its own receptors. Increase in body mass index (BMI) has a direct relationship with life length. Obesity has effects on secretion of some hormones related to adipokines. Adiponectin is an adipokine having an opposite relationship with insulin resistance and breast cancer. There is also an association between breast cancer incidence and obesity. Adiponectin level decreases in women affected by breast cancer and knowing this fact can help treat and prevent the cancer by giving adiponectin supplements. The present study compared the adiponectin levels in women affected by breast cancer and healthy females as a control group. Material and Method: In this study, 80 women with breast cancer and 80 healthy females as controls were selected and adiponectin level was compared between them. Result: Breast cancer group had higher BMI mean (28.77 ± 6.05) and lower adiponectin level in comparison to control group (p= 0.0001). Conclusion: Considering our findings, breast cancer risk is higher in women with higher BMI. Therefore, informing women in this regard could have a great effect on preventing this wide-spread disease. Taking adiponectin supplements as pills or injection could be a preventing step for breast cancer, which needs to be further cultivated in future studies.